2021
DOI: 10.4196/kjpp.2021.25.2.131
|View full text |Cite|
|
Sign up to set email alerts
|

Mangiferin ameliorates cardiac fibrosis in D-galactose-induced aging rats by inhibiting TGF-β/p38/MK2 signaling pathway

Abstract: Aging is the process spontaneously occurred in living organisms. Cardiac fibrosis is a pathophysiological process of cardiac aging. Mangiferin is a well-known C-glucoside xanthone in mango leaves with lots of beneficial properties. In this study, rat model of cardiac fibrosis was induced by injected with 150 mg/kg/d D-galactose for 8 weeks. The age-related cardiac decline was estimated by detecting the relative weight of heart, the serum levels of cardiac injury indicators and the expression of hypertrophic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…D-galactose, which is an aging agent, has been widely used in the construction of cell and animal models of premature aging, but its mechanism is not fully understood. Excessive intake of D-galactose can lead to cellular metabolism disorders, enzyme activity changes, and increased peroxides, leading to oxidative damage to the structure and function of biological macromolecules, which then leads to systemic inflammatory responses and various complications (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…D-galactose, which is an aging agent, has been widely used in the construction of cell and animal models of premature aging, but its mechanism is not fully understood. Excessive intake of D-galactose can lead to cellular metabolism disorders, enzyme activity changes, and increased peroxides, leading to oxidative damage to the structure and function of biological macromolecules, which then leads to systemic inflammatory responses and various complications (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal injection of D-galactose at a dose of 150 mg/kg/day in Wistar rats for eight weeks, or subcutaneous injection of D-galactose at a dose of 500 mg/kg/day in mice for four weeks increased the cardiac index and led to cardiac fibrosis. [28][29][30] This difference may be related to the dose and duration of D-galactose treatment. In conclusion, taking rats as an example, intraperitoneal injection of a higher dose of D-galactose and for a prolonged period leads to a decrease in the cardiac index.…”
Section: Effec Tofd -G Al Ac Tos E Adminis Tr Ati Ononthemarker Sof C...mentioning
confidence: 99%
“…13,[32][33][34][35][36] Moreover, studies have shown that heavier Wistar rats require higher amounts of D-galactose at the same administration time. 10,12,28,30,37 Evidence suggests that D-galactose treatment increases oxidants levels and decreases antioxidants levels (Table 2). ROS can attack proteins, lipids and DNA, altering their structures and functions.…”
Section: Effec Tofd -G Al Ac Tos E Adminis Tr Ationonc Ardiacoxidativ...mentioning
confidence: 99%
See 2 more Smart Citations